Association between anemia, mental health, and nutritional status among junior high school students: a cross-sectional study in Pontianak - Agustina Arundina Triharja Tejoyuwono; Iit Fitrianingrum; Desriani Lestari (International Journal of Public Health Science (IJPHS), 2026)
Iron deficiency can affect emotional regulation and contribute to symptoms of anxiety, stress, and depression. Poor dietary habits combined with mental health problems may further increase the risk of anemia. This study examined the association between anemia, mental health, and nutritional status among junior high school students in Pontianak. A cross-sectional design was used from May to December 2024 involving 277 students. Data were collected using body mass index (BMI) measurements, hemoglobin screening, and the DASS-Y questionnaire, and were analyzed with Spearman’s Rho. Most respondents were female (63.9%), and 90.96% had experienced menstruation. A total of 103 students were underweight, with an average mid–upper arm circumference of 21.48 cm, indicating chronic nutritional risk. Eighty-one students (29.2%) had anemia, predominantly females. Most students had good mental health (below the 50th percentile). No significant associations were found between anemia and mental health (p = 0.623) or between anemia and nutritional status (p = 0.664). Despite the lack of significant relationships, ongoing nutrition education, regular iron supplementation, counseling support, and routine monitoring of students’ nutritional and mental health remain important to maintain and improve overall wellbeing.